Financial stress and quit intention: the mediating role of entrepreneurs' affective commitment - Anne-Kathrin Kleine; Antje Schmitt; Barbara M. Wisse (International Entrepreneurship and Management Journal, 2024)
One primary reason why entrepreneurs abandon their entrepreneurial goals is due to pressing financial difficulties. In one experimental and two field studies, we investigated the relationship between entrepreneurs' financial stress and their intention to quit their businesses. In line with the challenge–hindrance stressor (CHS) framework, all three studies showed a positive link between financial stress and quit intention, both concurrently and over time. Furthermore, drawing on self-determination theory (SDT), we found support for affective commitment (but not continuance commitment) to the entrepreneurial endeavors as a mediator of the relationship. The findings provide novel insights into financial stress as a relevant entrepreneurial hindrance stressor and the role of the emotional bond formed (and dissolved) between entrepreneurs and their jobs as the mediating mechanism. Practical suggestions include considering the affective commitment levels of entrepreneurs to enhance consultancy and decision-making in entrepreneurship.
Keywords: 650; Entrepreneurship; Financial stress; Challenge-hindrance stressor; Job commitment; Quit intention